Basal cell carcinomas of the scalp after radiotherapy for tinea capitis: Clinicopathological study in a case series of 96 patients with analysis of 427 tumours. (28th October 2022) - Cardoso, José Carlos; Alves, Francisca; Calado, Rebeca; Batista, Mariana; Carreira, Isabel Marques; Tellechea, Oscar
Abstract: Background/Objectives: Low‐dose X‐ray radiotherapy to treat tinea capitis during childhood is a well‐known risk factor for scalp basal cell carcinomas (BCCs). Post‐radiotherapy BCCs are often multiple, and it has been suggested that they display more aggressive features. Our main objective was to study the clinicopathological aspects of post‐radiotherapy BCCs to evaluate their biological behaviour and identify features that may differ from other BCCs. Methods: We performed an observational, retrospective study assessing multiple clinical and pathological characteristics of patients with post‐radiotherapy BCCs. Results: We studied 96 patients with 427 post‐radiotherapy scalp BCCs. Post‐radiotherapy BCCs were often multiple (median of 4 lesions/patient, ranging from 1 to 54). Significant comorbidities included a high incidence of thyroid disease and meningiomas. Recurrences were observed in 23% of patients, but there may be confounding factors, such as referral bias, heterogenous treatment modalities and occurrence of new tumours due to field effect. We found a high incidence of infundibulocystic BCCs (in 14.6% of patients and corresponding to 5.4% of the total number of tumours), trichoblastomas (5.2%) and neurofibromas of the scalp (10%). Conclusions: This study is consistent with the occurrence of multiple lesions (sometimes numerous) and a relatively high tendency for recurrence in post‐radiotherapy BCCs, as suggested by previous studies. We also found a high incidence of the infundibulocystic variant and a higher risk of follicular tumours and neurofibromas, which suggests that radiotherapy may influence the type of differentiation of BCCs and contribute to induce neoplasms of different cell lines.